A pilot clinical and radiographic study on the association between periodontitis and serious COVID‐19 infection - Panagiotis Gardelis; Alkisti Zekeridou; Noemie Suh; Christophe Le Terrier; Andreas Stavropoulos; Catherine Giannopoulou (Wiley, 2022)
Abstract Background During the pandemic of COVID‐19, the scientific community tried to identify the risk factors that aggravate the viral infection. Oral health and specifically periodontitis have been shown to have a significant impact on overall health. Current, yet limited, evidence suggests a link between periodontal status and severity of COVID‐19 infection. Objectives The present pilot study aimed to assess whether younger patients (≤60 years) that have been hospitalized in the intensive care unit (ICU) for severe COVID‐19 infection were susceptible to severe periodontitis. Material and Methods All dentate patients ≤60 years of age diagnosed with COVID‐19 and surviving hospitalization in the ICU were considered for inclusion. Susceptibility to periodontitis was determined by assessing radiographic bone loss (RBL) in recent dental radiographs (posterior bitewings, periapical, and panoramic X‐rays). RBL in % was obtained from the most affected tooth and patients were classified into: Stage I, RBL ≤ 15%; Stage II, RBL = 15%−33% and Stage III/IV, RBL ≥ 33%. The grade was defined using the RBL to age ratio on the most severely affected tooth. Patients were attributed to: Grade A, ratio <0.25; Grade B, ratio 0.25−1 and Grade C, ratio >1. Patients classified into Stage III/IV and Grade C were considered highly susceptible to periodontitis. Results Of 87 eligible patients, 30 patients were finally assessed radiographically and/or clinically; from the remaining 57 patients, 16 refused participation for various reasons and 41 could not be reached. Based on the radiographic assessment, all patients were periodontally compromised. Half of them were classified with Stage III/IV and Grade B or C; 26.7% were classified with Stage III/IV and Grade C. Conclusions The present pilot study showed that about half of the patients suffering from severe forms of COVID‐19 infection in need of ICU admission suffered also from severe periodontitis, and about one‐fourth of them were highly susceptible to it.